The association between polymorphism of the long noncoding RNA, Plasmacytoma variant translocation 1, and the risk of gastric cancer. Issue 48 (3rd December 2021) - Park, Jae Ho; Jin, Eun-Heui; Hong, Jang Hee; Lee, Sang-Il; Sung, Jae Kyu
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Genetic polymorphisms of plasmacytoma variant translocation 1 can affect various tumors including gastro-intestinal, sexual hormone sensitive cancers and lymphoma. Accumulated evidence have shown that plasmacytoma variant translocation 1 acts as an oncogene and tumor suppressor in various cancers. In fact, the rs13255292 and rs2608053 single nucleotide polymorphisms of plasmacytoma variant translocation 1are known to affect lymphoma; however, their effects on gastric cancer are primarily unknown. In this study, we evaluated the association between these plasmacytoma variant translocation 1 polymorphisms and the risk of gastric cancer. In the present study, 462 patients diagnosed with gastric cancer and 377 cancer-free controls were enrolled. The TaqMan genotyping assay was used to analyze the association between rs13255292 and rs2608053 single nucleotide polymorphisms and the risk of gastric cancer. The rs2608053 dominant model (CT + TT) was associated with a decreased risk of gastric cancer in T3 + T4 (odds ratio [OR] = 0.61, confidence interval (CI) = 0.41 – 0.92, P  = .019), and stage III Gastric cancer subgroups (OR = 0.59, 95% CI = 0.38 – 0.91, P  = .017) compared to the CC genotype. When stratified analysis by sex was carried out, the rs13255292 dominant model (CT + TT) had a significant association with an increased risk of gastric cancer in the female negative lymph node metastasis gastric cancer subgroup, compared to the CC genotype (OR = 1.96, 95% CI = 1.16 – 3.30, P  = .012). The recessive model (TT) of rs13255292 was associated with an increased risk of gastric cancer in the male T3 + T4 gastric cancer subgroups compared to the CC + CT genotype (OR = 3.82, 95% CI = 1.02 – 14.33, P  = .047). The dominant model (CT + TT) of rs2608053 was related to a decreased risk of gastric cancer in male T3 + T4 (OR = 0.57, 95% CI = 0.33 – 0.98, P  = .042) and stage III gastric cancer subgroups (OR = 0.49, 95% CI = 0.27 – 0.89, P  = .020) compared to the CC genotype. The rs13255292 and rs2608053 single nucleotide polymorphisms in plasmacytoma variant translocation 1 may contribute to susceptibility of gastric cancer. Further studies with more subjects and different ethnic groups are needed to validate our results.